A Review of Complications in Patients Receiving Cosmetic Dermatology (International Journal of Food and Nutritional Sciences, 2022)
Background: In recent years, patients have had a remarkably wide range of alternatives for aesthetic rejuvenation. Neuromodulators, fillers, sclerotherapy, chemical peels, liposculpture, lasers, lights, and other energy devices are just a few of the alternatives that are frequently offered to patients today. These cosmetic dermatological procedures do carry some risk, as with any therapeutic therapies. For the best patient outcomes, problems must be identified and treated promptly.Objectives: This review's first section will concentrate on the typical side effects of injectable cosmetic procedures such neuromodulators, fillers, and sclerotherapy. The problems of chemical peels, lasers, light and energy sources, and fat removal methods will be covered in the second section.Methods and Materials: The findings of a MEDLINE search on cosmetic dermatology problems from 1989 to 2015 are compiled here. These problems' practical considerations are also offered.Results: There have been reports of complications following the use of neuromodulators, injectable hyaluronic acid, calcium hydroxylapatite, poly-L-lactic acid, polymethylmethacrylate, sclerotherapy, fat transfer, liposuction, cryolipolysis, chemical peels, lasers, and light sources like Q-switched lasers, intense pulsed light, nonablative, and ablative resurfacing lasers.Conclusion: A review of the literature found a variety of alternatives for treating potential side effects from the numerous cosmetic dermatological procedures that are currently offered to patients.